2013
DOI: 10.1002/app.39848
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characteristic of a sodium alginate/carboxymethylated bacterial cellulose composite with a crosslinking semi‐interpenetrating network

Abstract: A novel ionic crosslinking sodium alginate (SA)/carboxymethylated bacterial cellulose (CM‐BC) composite with a semi‐interpenetrating polymer network (semi‐IPN) structure was developed in this study. The composite was prepared through the blending of an SA gel with CM‐BC then crosslinking by Ca2+ followed by a freeze‐drying process. Scanning electron microscopy showed the composite matrix organized in a three‐dimensional network of CM‐BC interpenetrated against SA molecular chains with a quantity of calcium alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…This composite presented outstanding swelling ratios, tensile modulus, tensile strength and elongation when compared with pure BC. This study confirmed that the interpenetrating structure radically changes the swelling and mechanical properties of the composite and enables it as a promising candidate for biomedical applications as wound dressings and skin tissue engineering (Lin et al ., ). It is known that dried BC possesses poor gas permeability and water absorption.…”
Section: Bacterial Cellulose Compositesmentioning
confidence: 97%
See 1 more Smart Citation
“…This composite presented outstanding swelling ratios, tensile modulus, tensile strength and elongation when compared with pure BC. This study confirmed that the interpenetrating structure radically changes the swelling and mechanical properties of the composite and enables it as a promising candidate for biomedical applications as wound dressings and skin tissue engineering (Lin et al ., ). It is known that dried BC possesses poor gas permeability and water absorption.…”
Section: Bacterial Cellulose Compositesmentioning
confidence: 97%
“…In most cases, these properties could not be achieved with the isolated base component. The reinforcing phase, which may consist of fibres (Lazarini et al ., ), particles (Galateanu et al ., ), sheets (layers) (Foong et al ., ), interpenetrating networks (Lin et al ., ) or cells, is dispersed in the so‐called matrix or continuous phase (usually the one presenting a higher percentage). The properties of the composites depend on both the nature of the materials employed and the degree of bonding between them through the interface.…”
Section: Bacterial Cellulose Compositesmentioning
confidence: 99%
“…Wound dressing should maintain the temperature of the wound bed (not evaluated) and has to accelerate the process of wound healing, as well as reduce the debris influence on the healing process. The suitably designed dressing would also preserve the gaseous exchange and would protect the newly restored tissue [26,55]. Nowadays designed dressings should also reduce patients' pain (by covering and protecting ends of the nerves) and discomfort associated with wearing the dressing [56].…”
Section: Bacterial Cellulose For Wound Moisturementioning
confidence: 99%
“…The swelling capacity was enhanced with the increase of bacterial cellulose content up to 212 %, as well as thermal properties, which revealed the increment of the onset degradation temperatures from 146°C for native sodium alginate gel up to 187°C for its composites with bacterial cellulose. Moreover, the possibility to introduce drugs into composite structure was identified which would allow to use this composition as a wound dressing material [55] of improved BC antibacterial activity in case of suitable substances application.…”
Section: Natural Compounds As a Solution For Poor Bc Antimicrobial Acmentioning
confidence: 99%
“…Alginate/Carboxymethylated BC/crosslinking with calcium [95] The composite has dramatically improved in the swelling, thermal & mechanical properties. Application: wound dressings and skin tissue engineering Alginate/BC/Silver sulfadiazine [96] The composite has an excellent antibacterial activities & good biocompatibility.…”
Section: Preparation Of Seaweed/cellulose Blendsmentioning
confidence: 99%